Integrating FSF into Farming Systems and Value Chain Development Promoting Agriculture Diversification: A Case Study at the Provincial Level - Phouyyavong, Khamphou (2018)
Khamphou Phouyyavong IFPRI-FAO conference side event, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand